(untitled) (Jurnal Teknologi Industri Pertanian, 2017)
Growing population make public consumtion in term of foods becoming more complex, resulting in the opportunities to produce new product. One of them is producing new product from vegetables, which is now widely grown variety of organic vegetables. This is an opportunity to produce a new product are made from organic spinach. The purpose of this research is to identify the characteristics of a new product of organic spinach puree; analyze consumer preference; and formulate marketing strategies on the new product of organic spinach puree. In this research, the analysis performed includes descriptive analysis; conjoint analysis to know consumer preference consisting of packaging and flavors; and Analytical Hierarchy Process (AHP) to formulate marketing strategy for the new product of organic spinach puree. The result showed that as many as 96 respondents of 100 total respondents used as the sample claimed to be interested in the new product. The analysis result of consumer preference using conjoint analysis show that the packaging is the most important attribute for consumer to make purchasing decision. For the best combination of choice attributes is organic spinach puree with melon flavors and packaging in sachet. According to the AHP method which has been done, a strategy to strengthen business colaborations or partnerships is an alternative strategy to be a priority in the marketing of organic spinach puree. Keywords: analytical hierarchy process, consumer preference, marketing strategy, organic spinach puree